Lion swarm optimization for grid connected PV system with improved SEPIC - Annapandi, P.; Lakshmi, D.; Santhoshi, B. Kavya; Annapoorani, P. (International Journal of Applied Power Engineering (IJAPE), 2024)
The wide deployment of grid-connected renewable energy system has piqued immense attention recently, in response to rising electricity consumption, diminishing fossil fuel reserves in addition to the need for reducing carbon emissions. Among the available sources of renewable energy, photovoltaic (PV) power generation is the most promising technology with enormous potential and easy access. This paper presents an optimum control technique for grid connected PV systems. The improved single ended primary inductor converter (SEPIC) controls and regulates PV output power to the optimum voltage level. The working of the improved SEPIC is controlled by a proportional-integral (PI) controller optimized by meta-heuristic technique of lion swarm optimization (LSO). The constant output from the converter is then supplied to the power grid through a single-phase voltage source inverter (1? VSI). The effectiveness of the proposed control strategy is ascertained using hardware validation with DSPIC3050FPGA controller and MATLAB simulation generating a reduced total harmonic distortion (THD) of 3.9% and 2.9%, respectively. Furthermore, the proposed system generates an enhanced voltage gain of 1:10 and an efficiency of 96%.